Statistical modelling for rainfall time series analysis: Khurdha district of Odisha, India - Ankita Bohidar; Anil Kumar Kar; Pradip Kumar Das (PREPARE@u® | IEI Conferences, 2021)
The rainfall at Odisha state is monsoon driven. The capital city of Odisha state is Bhubaneswar which lies at Khurdha district. In this study, a statistical modeling is done for the monsoon rainfall of this district including frequency analysis of the monsoon rainfalls using L-moment techniques. The randomness of the data is determined from Anderson Correllogram test and then the existence of probable trend is determined using non-parametric test like Mann Kendall. All the datasets are found to be random but the rainfall during August shows a rising trend at all 1, 5 and 10% significance level. Also in month July it rises 5 and 10% Significance level. The forecasting of the monthly rainfall is made through an Auto Regressive Moving Average (ARMA) model. The ARMA (1,1) combination hold good for  months of June, July and September, August and October ARMA (1,2) ARMA (3,3) respectively show better result. Akaike Information Criteria (AIC) has been used for evaluating the performance of ARMA models. The study shows the statistical application on climate data and the results are advisory and indispensable for making useful and reliable decisions in hydrological forecasting and planning.